PENENTUAN PUSAT PERTUMBUHAN EKONOMI DAN IDENTIFIKASI INTERAKSI EKONOMI SEKTORAL PADA KAWASAN SEGITIGA EMAS TAHUN 2016-2020 - risma amelia; Prayudi Setiawan Prabowo (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The reason of this study became to decide the center of economic growth and to identify sectoral economic interactions in the Golden Triangle Region (Lamongan, Tuban and Bojonegoro Regencies). The analytical tools used are scalogram analysis, shift-share and gravity analysis. The effets of the scalogram analysis display that Bojonegoro Regency is the center of growth, with the number of facility units being 1969. Based at the effects of the shift-share evaluation calculating, it is found that Lamongan Regency has the highest competitive advantage, namely the manufacturing sector has differential shift calculation of 662289.02 and makes the processing industry has the best value compared to other elements. Bojonegoro Regency has the highest competitive advantage, namely the mining and quarrying region, with fee of 6287922.64, Tuban Regency with the highest competitive advantage is the agriculture, forestry and fishery sector with value of 91334.11. And base totally at the calculation of gravity evaluation, it indicates that the very best attractiveness is between Bojonegoro Regency and Lamongan Regency.